Standarisasi Prosedur Koordinasi Antara Unit APP dan Tower dalam Menggunakan Sistem Freetext di Perum LPPNPI Cabang Pontianak - Saraswati, Ni Putu Tiara; Saputra, Surya Tri (Jurnal Bisnis dan Operasi Penerbangan, 2024)
In the activity of providing air traffic services, the Pontianak Approach Control Surveillance unit has implemented ATC automation. One of them is the coordination carried out by ATC personnel between the APP unit and the Tower unit. The coordination uses a system called free text. The free text system can facilitate the ATC coordination process, especially between ATC personnel from the APP unit and the Pontianak Branch of the Perum LPPNPI Tower unit, because it can reduce load of communication. However, the SOP of Perum LPPNPI Pontianak Branch has not yet found a procedure regarding standardization of words to coordinate using this free text system. This study aims to form a standardization of writing words in the free text system between Pontianak Approach Control Surveillance and Pontianak Tower. The method used in this research is descriptive qualitative. The results of this study suggest that there is a need for standardization of words to coordinate using the free text system between Tower units and APP units at Perum LPPNPI Pontianak Branch.